Energy Efficiency in Backbone Networks. (3rd July 2015) - Eyupoglu, Can; Aydin, Muhammed Ali
Abstract: The topic of energy efficiency in backbone networks has recently gained an increasing interest and has become one of the important parts of networking research. The energy consumption of current electronic devices is increasing too fast with the continuous growth of the Internet traffic. In addition, Information and Communications Technologies (ICT) consume the worldwide energy ranging from 2% to 10% and the consumption of ICT will almost double by 2020. According to many studies, the Internet will use 50% of the world electricity in the near future. In this study, energy efficiency of backbone networks is examined. Besides, the techniques recently used for energy saving in backbone networks are analyzed.